Do social factors influence investment behavior and performance? Evidence from mutual fund holdings - Borgers, Arian; Derwall, Jeroen; Koedijk, Kees; ter Horst, Jenke (Journal of Banking & Finance, 2015)
We study the economic significance of social dimensions in investment decisions by analyzing the holdings of U.S. equity mutual funds over the period 2004–2012. Using these holdings, we measure funds’ exposures to socially sensitive stocks in order to answer two questions. What explains cross-sectional variation in mutual funds’ exposure to controversial companies? Does exposure to controversial stocks drive fund returns? We find that exposures to socially sensitive stocks are weaker for funds that aim to attract socially conscious and institutional investor clientele, and they relate to local political and religious factors. The financial payoff associated with greater “sin” stock exposure is positive and statistically significant, but becomes non-significant with broader definitions of socially sensitive investments. Despite the positive relation between mutual fund return and sin stock exposure, the annualized risk-adjusted return spread between a portfolio of funds with highest sin stock exposure and its lowest-ranked counterpart is statistically not significant. The results suggest that fund managers do not tilt heavily towards controversial stocks because of social considerations and practical constraints.